Police Rhetorics and Rhetorical Self-Awareness, and Their Contributions to Cultural Contexts of Policing in the Higher Education Campus Setting - Sugg, Jason Lee (East Carolina University)
It is widely accepted that the notion of occupational cultures exists in various forms. Arguably, highly organized professions and workplaces are some of the most encultured spaces in terms of contextual occupational cultures. Not least among them is the policing profession. Inclusive to notions of occupational culture is the idea that occupational culture exists in a manner that is driven by discourses, contexts, understandings, and meanings that are relevant to those who occupy those occupational spaces. The purpose of this qualitative study, backgrounded by a cultural rhetorics lens, is to explore and articulate the notion of "police rhetorics" as a particularized discourse practice amongst police officers and police agencies. This study also seeks to determine police officer rhetorical self-awareness levels and conclude contributory factors of police rhetorics and rhetorical self-awareness to the contextual understanding of policing in the higher education setting. Because campus policing is relatively understudied this study focuses on campus police officers currently employed in the University of North Carolina (UNC) System, of which there are 17 separate institutions, and more than 450 police officers employed. The study consists of one-on-one interviews with currently employed campus police officers of varying years of experience and varying levels of leadership roles. The results largely indicate a high level of recognition amongst the officers of police as well as a high level of rhetorical self-awareness. The results also indicate a general high-level understanding of how their rhetorical positionality impacts the cultural contextual understanding of the police role on a campus of higher education. Takeaways from the study include discussion and conclusions made about police officers' roles and recognition of their rhetorical discursive practices, and self-recognition of the impacts of their roles in how policing is contextualized in a campus community's cultural perspectives. Cultural perspectives and understanding are impacted by police interactions, behaviors, and discourse, and influences how policing is understood in that community. Conversely, cultural contexts of policing inform police interactions, behaviors, and discourse. The resulting exchange of perception and rhetorical impacts is supported by cultural rhetorics application in that cultural rhetorics recognizes that rhetoric is culture and culture is rhetoric.
Keywords: cultural rhetorics; police rhetorics; rhetorical self-awareness; higher education; campus culture; cultural contexts; Campus police--North Carolina--Attitudes; College environment--North Carolina; Law enforcement--North Carolina--Terminology; Rhetoric--North Carolina; Self-perception